Pengaruh Video Edukasi Perawatan Payudara Menggunakan Media Phantom Terhadap Kualitas Sekresi ASI Ibu Menyusui Di Dusun Waimolong Desa Hitumessing Kecamatan Leihitu Kabupaten Maluku Tengah - Malawat, Ratna; Rahmawati, Wa Ode; Ratulohain, Christina Lorince (Jurnal Kesehatan Terpadu (Integrated Health Journal), 2024)
Breast milk production and excretion can be influenced by several factors, namely breast care, frequency of breastfeeding, parity, stress, maternal illness or health, nutritional intake, consumption of cigarettes or alcohol and contraceptive pills. In the process, breastfeeding can also be accompanied by various problems. Thus, every mother needs to take care of her breasts when breastfeeding. Along with the increasing use of gadgets in society, educational videos are a very effective medium to use in the learning process. Mothers can easily learn via gallery gadgets and social media. mothers can learn and know breast care techniques and are willing to do it independently and do not need to leave their babies. This research aims to determine the effect of breast care educational videos using phantom media on the quality of breast milk secretions of breastfeeding mothers in Hitumessing Village, Leihitu District, Central Maluku Regency. This type of research is experimental with a Post-test Only Control Group Design. Samples were taken using purposive sampling technique. The data analysis technique uses the independent t test. The research was conducted in August – October 2024. The research sample consisted of 30 people who were divided into two groups consisting of 15 intervention respondents and 15 respondents from the control group. The results of this study show that there is a significant influence between breast care educational videos using phantom media on the quality of breast milk secretion, the average increase in breast milk secretion volume was 119.67 ml in the intervention group while the control group was only 59.33 ml. Based on statistical analysis it was found that ha was accepted. So there is an influence between breast care educational videos using phantom media and the quality of breast milk secretions of breastfeeding mothers, where the p value = 0.000 (<0.05).